The thoracic sclerites of Belostoma Latreille (Hemiptera: Belostomatidae) and their usefulness for species identification - Estevez, Ana L.; Schnack, Juan A.; de Reyes, Cristina A. (Zootaxa, 2006)
Some thoracic sclerites, including the mesepimeron, postalar projection, wing knob, metanotum pubescence, and wing groove widening, are described and analyzed as worthy taxonomic characters for the identification of adult species of the genus Belostoma Latreille 1807. We tested the diagnostic value of these structures on specimens of B. dentatum (Mayr, 1863), B. elegans (Mayr, 1871), B. micantulum (Stål, 1860), and B. oxyurum (Dufour, 1863).